2015
DOI: 10.3923/ajar.2015.293.304
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Anti-Microbial Activities of Selected Honey Samples

Abstract: The medical property of honey in wound healing was reported due to its anti-inflammatory and anti-microbial activities. It is believed that polar compounds including sugars and polyphenols in honey could contribute to the biological activities. In this study, crude honey samples of Tualang, Gelam and Acacia were fractionated into polar fractions using a C18 reversed-phase extraction column. The polar fractions were found to be more effective than crude honey samples because of lower effective concentration (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…The anti‐tyrosinase activity of two SHs from different regions of Thailand was found as 46.64 % and 52.12 % [25] . Tualang, Gelam, Acacia, and Manuka honeys from Malaysia were investigated for anti‐inflammatory on COX‐1 (EC 50 : 1.285–6.130 g/mL) and COX‐2 1 (EC 50 : 0.333–3.050 g/mL) [62] . Tyrosinase inhibition activities of Arbutus (IC 50 : 119.7±5.2 mg/mL), Asphodelus (IC 50 :>200 mg/mL), Eucalyptus (IC 50 : 157.7±2.5 mg/mL), Thistle (IC 50 : 64.3±1.6 mg/mL), and Sulla (IC 50 :>200 mg/mL) honeys from Italy was reported by Di Petrillo et al [63] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti‐tyrosinase activity of two SHs from different regions of Thailand was found as 46.64 % and 52.12 % [25] . Tualang, Gelam, Acacia, and Manuka honeys from Malaysia were investigated for anti‐inflammatory on COX‐1 (EC 50 : 1.285–6.130 g/mL) and COX‐2 1 (EC 50 : 0.333–3.050 g/mL) [62] . Tyrosinase inhibition activities of Arbutus (IC 50 : 119.7±5.2 mg/mL), Asphodelus (IC 50 :>200 mg/mL), Eucalyptus (IC 50 : 157.7±2.5 mg/mL), Thistle (IC 50 : 64.3±1.6 mg/mL), and Sulla (IC 50 :>200 mg/mL) honeys from Italy was reported by Di Petrillo et al [63] .…”
Section: Resultsmentioning
confidence: 99%
“…[25] Tualang, Gelam, Acacia, and Manuka honeys from Malaysia were investigated for anti-inflammatory on COX-1 (EC 50 : 1.285-6.130 g/mL) and COX-2 1 (EC 50 : 0.333-3.050 g/mL). [62] Tyrosinase inhibition activities of Arbutus (IC 50 : 119.7 � 5.2 mg/mL), Asphodelus (IC 50 : > 200 mg/mL), Eucalyptus (IC 50 : 157.7 � 2.5 mg/mL), Thistle (IC 50 : 64.3 � 1.6 mg/mL), and Sulla (IC 50 : > 200 mg/mL) honeys from Italy was reported by Di Petrillo et al [63] Inhibition values of AChE, BChE, urease and tyrosinase of 37 different Astragalus honeys from Turkey at 20 mg/mL concentration were calculated as 7.40 � 0.36-30.35 � 0.86 %, not active-18.22 � 0.68 %, 14.80 � 0.56-70.42 � 0.96 %, 13.65 � 0.27-51.32 � 0.87 %, respectively. Also, high COX-1 (46.20 � 0.27-76.11 � 0.80 %) and COX-2 (34.20 � 0.51-55.98 � 0.93 %) inhibition activities were found for all studied Astragalus honeys at 25 mg/mL concentration.…”
Section: Anticholinesterase Anti-urease Anti-tyrosinase and Antiinfla...mentioning
confidence: 99%
“…For instance, Brazilian honey and Malaysian Tualang honey exert significant anti-inflammatory activity by reducing edema formation, inhibiting leukocyte migration, and decreasing the production of reactive oxygen species (ROS) and cyclooxygenase-2 activity (COX-2). [1,16] On the other hand, Malaysian Gelam honey controls inflammation through tight regulation of the nuclear factor kappa B (NF-κB) pathway including its downstream targets like tumor necrosis factor-α (TNF-α), prostaglandin E 2 (PGE 2 ), interleukin 1β (IL-1β), interleukin 6 (IL-6) and nitric oxide (NO). [17][18][19] Meanwhile, Manuka and jelly bush honey from New Zealand and Australia respectively display potent anti-inflammatory properties by impeding the activation of COX-2 as well as inducible nitric oxide synthase (iNOS), and decreasing the synthesis of prostaglandins and inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent study, Kelulut honey resulted in lower minimum inhibitory concentration (MIC) to inhibit common pathogenic bacteria species of P. aeruginosa indicating higher antibacterial properties compared to manuka honey (Mohd-Aspar et al, 2020). There were studies reported on the factors that contribute to the antibacterial properties of Malaysian honey, which are generally due to acidity and the presence of peroxide (Zainol et al, 2013;Jalil et al, 2017) and non-peroxide compounds (represented by phenolic and flavonoid compounds) (Chua and Ismail, 2015;Tuksitha et al, 2018). However, the active contribution of these factors towards the antibacterial properties of the honey was questionable and there are limited data to support the active contribution of the factors on antibacterial properties of Malaysian honey, which limit the understanding (Roslan et al, 2015;Shehu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%